Comparison of the safety and efficacy of a fixed-dose combination regimen and separate formulations for pulmonary tuberculosis treatment - Wu, Jiun-Ting (2015)
OBJECTIVES: Fixed-dose combination formulations, which simplify the administration of drugs and prevent the development of drug resistance, have been recommended as a standard anti-tuberculosis treatment regimen. However, the composition and dosage recommendations for fixed-dose combination formulations differ from those for separate formulations. Thus, questions about the effectiveness and side effects of combination formulations remain. The aim of this study was to compare the safety and efficacy of these two types of anti-tuberculosis regimens for pulmonary tuberculosis treatment. METHOD: A prospective, randomized controlled study was conducted using the directly observed treatment short-course strategy. Patients were randomly allocated to one of two short-course regimens. One year after completing the treatment, these patients’ outcomes were analyzed. ClinicalTrials.gov: NCT00979290. RESULTS: A total of 161 patients were enrolled, 142 of whom were evaluable for safety assessment. The two regimens had a similar incidence of adverse effects. In the per-protocol population, serum bilirubin concentrations at the peak level, at week 4, and at week 8 were significantly higher for the fixed-dose combination formulation than for the separate formulations. All patients had negative sputum cultures at the end of the treatment, and no relapse occurred after one year of follow-up. CONCLUSIONS: In this randomized study, transient higher serum bilirubin levels were noted for the fixed-dose combination regimen compared with the separate formulations during treatment. However, no significant difference in safety or efficacy was found between the groups when the directly observed treatment short-course strategy was used.